Загальні поняття адміністративного примусу та особливості його застосування міліцією - Коваленко, І.; Kovalenko, I. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті розглянуто загальне поняття державного й адміністративного примусу, особливості його застосування міліцією. Звернено увагу на регулювання суспільних відносин, яке здійснює держава правовими засобами та яке, як правило, носить характер примусу. Одним із видів державного примусу є адміністративний, що застосовується міліцією до правопорушників у випадках і в порядку, зазначеному в законі. The article considers the definition of public and administrative coercive means as well as the peculiarities of their use by police. The main attention is paid to the state settlement of public relations by means of legal measures. As a rule such settlement is of the coercive nature. The dministrative pressure is regarded to be one of the types of state coercive means, which is used by the police to offenders in accordance with the law. The use of the ways and means by the police aimed at the preventing the crime as well as preventing the occurrence of circumstances that threaten the public safety of the citizens are viewed as the measures of the administrative preventing of offenses. The preventing measures are defined as compulsory ways for combating the wrongful acts with the signs of an administrative offense. Administrative sanctions are viewed as practical means of realization of administrative liability for committing administrative offenses.
The General Issues of the Administrative Coercive Means and the Peculiarities of Their use by Police
Keywords: державна влада; міліція; громадський порядок; state enforcement; police; public order